Small Business Maneuvering: The Efficacy of Synergized Innovation, Talent Management, and Impeding Culture for Improved Performance - Dianingrum, Melia; Rabiatul Adawiyah, Wiwiek; Zulaikha Wulandari, Siti (Jordan Journal of Business Administration, 2025)
The purposes of this study are: examining the effect of talent management on organizational performance being mediated by a synergized innovation climate and investigating the moderating power of organizational culture in the relationship between talent management and organizational performance. This study reports the responses of 292 owners of SMEs in Indonesia. The structural equation modeling (SEM) technique was used to test the hypotheses. Our findings fail to support the view that talent management has a positive effect on organizational performance. Synergized innovation climate appears to mediate the relationship between talent management and small business performance. In addition, organizational culture strengthened the relationship between talent management and organizational performance. Our research extends the application of cognitive social theory, whereby talent management functions as a value-adding activity within small business firms.